Physical Activity and Body Composition in Norwegian Adolescents. Results from The Tromsø Study: Fit Futures - Aars, Nils Abel (UiT The Arctic University of Norway, 2021)
The present thesis has investigated the cross-sectional and prospective associations between self-reported and objectively measured physical activity with five objectively measured indices of body composition in Norwegian adolescents participating in the Tromsø Study Fit: Futures Cohort. The three included papers used regression analyses to assess the cross-sectional association between self-reported physical activity and body composition in first year of upper secondary high school, and whether self-reported or objectively measured physical activity predicted changes in body composition between first- and last year of upper secondary high school. A significant cross sectional association was observed between self-reported physical activity and waist circumference (girls only), fat- and lean mass index for both sexes, but self-reported physical activity generally did not predict changes to body composition between baseline- and follow-up. Changes in level of physical activity during follow-up was predictive of changes in fat mass index in boys and lean mass index in girls. Objectively measured physical activity at baseline did not predict changes in body composition in boys, whereas time spent in sedentary- and light intensity predicted changes in indices of lean mass in girls. No association was observed with BMI in either of the included papers. The findings are interpreted in light of the substantial changes that occur in both habits and body composition during adolescence, and shows that there are health benefits of remaining- or becoming physically active during this period.